Założenia epistemologiczne wykorzystania teorii zbiorów przybliżonych w ocenie i selekcji informacji klinicznych - Rzepiński, Tomasz (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2013)
The purpose of the present paper is to discuss the most basic intuitions that are connected with using rough set theory when evaluating clinical data. Furthermore, the article examines the espistemological assumptions that have to be made when the method is applied in formulating decision algorithims in clinical practice.
Keywords: clinical decision making; randomized control trials; rough set theory; epistemology